Spontaneous institutions: a typology - Karol Bolko Zdybel (European Journal of Law and Economics, 2025)
The paper offers a concise typology of spontaneous institutions – i.e., institutions formed or sustained through decentralized collective behavior in a community. It combines three commonly encountered criteria for determining what counts as a spontaneous institution: (i) implicit formation of (customary) rules, as opposed to the deliberate design of rules; (ii) lack of third-party enforcement; (iii) lack of third-party assessment of compliance with rules or third-party rule validation, as opposed to third-party interpretation of compliance. The typology is subsequently illustrated with examples derived from legal history, legal anthropology, and international law. Supposedly dissimilar normative systems (e.g., customary international law and primitive law; historically emergent rules of warfare and domestic social norms) are shown to exhibit structural resemblance. Finally, the paper discusses how various types of spontaneous institutions can be represented game-theoretically. In sum, the paper conceptually organizes the dissipated field of research of spontaneous institutions from the law and economics perspective.
Keywords: B41; H11; K00; N40; O17; 340; Private ordering; Informal institutions; Spontaneous order; Customary law; Social norms